Analysis of the Implementation of the Death Penalty in Corruption Cases in Indonesia - Emirza Henderlan Harahap (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses the phenomenon of increasing corruption cases in Indonesia, which is caused by the lack of effective criminal penalties. Although Law No. 20/2001 concerning the Eradication of Corruption regulates the threat of the death penalty for perpetrators of corruption, in practice it has never been implemented. This study uses the approach of the law enforcement system theory and the theory of punishment, with normative legal methods and literature studies. The results show that the difficulty of implementing the death penalty in corruption cases in Indonesia is caused by the pros and cons and rejection from the community and law enforcement. This finding indicates the importance of reforming the death penalty policy for perpetrators of corruption to provide a deterrent effect and prevent similar cases in the future. Therefore, this study recommends improving the law enforcement system and more effective anti-corruption policies.